PENGARUH LINGKUNGAN KERJA NON MEDIS DAN MOTIVASI KERJA TERHADAP KEPUASAN KERJA PEGAWAI RUMAH SAKIT JIWA TAMPAN KOTA PEKANBARU - Ramadhani, Nadia; Andri, Senox (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
This study aims to determine the influence of the work environment and motivation on job satisfaction of employees at the Tampan Mental Hospital, Pekanbaru City, partially and simultaneously. This research used a questionnaire as a data collection tool which was distributed to 117 respondents. The data analysis technique used is multiple linear regression, hypothesis testing, and determination efficiency using SPSS 16. Based on research results, the work environment partially influences the job satisfaction of employees at the Tampan Mental Hospital, Pekanbaru City. Motivation partially influences job satisfaction of employees at the Tampan Mental Hospital, Pekanbaru City. work environment and motivation simultaneously or together on the job satisfaction of employees at the Tampan Mental Hospital, Pekanbaru City Keywords: Work Environment, Motivation, Job Satisfaction